Gynecological endoscopic surgery in Cienfuegos. - Alberto Jorge Fernández; Alexis Díaz Brito; Israel Sotolongo Castro; Gabriel Jiménez González; Rafael Alejandro Gómez Baute (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
Background: In the last few years less invasive techniques for patients have been developed and endoscopic surgery is important example. Objective: To determine the advantages of endoscopic surgery and to relate ultrasonographic findings with surgical diagnoses. Method: Case study of 73 surgeries performed by gynaecological endoscopic surgery at the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ from Cienfuegos province in the period January 1998- May 2002. urgencies and and Salpingoclasias were excluded from this search. The statistical study included tests of percentage, accumulated frequency, Kappla´s index, mean and standard deviation. Results: The most recent gynaecological pathologies were: Pelvic Inflammatory Disease, infertility and ovarian cyst. The relationship between ultrasonographic and surgical diagnosis was good for P.I.D and the intrauterine device in the abdominal cavity but not for endometritis. The most frequent laparoscopic procedures were salpingovariolasis and fimbrioplasty , ovarian cystectomy and contrasted laparoscopy. The two complications were bleeding which was controlled and facial subcutaneous emphysema.